Review the View of the School of Separation in the Materiality of the Soul - mohammad hasan yaghoobian (حکمت اسرا)
The viewpoint of the separation school is the materiality of the soul, which claims to extend the viewpoints of the early theologians, and deals with two negative and positive approaches. The first approach is to criticize the philosophical view of the immortality of the soul and the second approach has been attempted by the rational arguments to prove the material element and the dark essence of the soul. The issue of this research is to analyze and review the view of this school by focusing on the positive approach that has been analyzed and criticized this issue. Therefore, the study of their mistakes and critique of the philosophical arguments of the immortality of the soul is beyond the scope of this article. The findings suggest that, regardless of the variety of epistemic perspectives in the early theologians, the claim of monopoly of immortality to God due to the contradiction between the creator and the creature has gradually diminished and reduced to some creatures. The rational admonitions are either criticized or controversial. Traditional narratives also lack consensus on the materiality of the soul. The intrinsic incompatibility of the quality of the material of soul and its distributions and the confrontation with the opposite view, in the dualism of the soul and body, is another problem in this view.